Suicidality and self-compassion in patients with major depressive disorder: the mediating role of the avoidant attachment type - Vasiliki Yotsidi; Charis Ntakolia; Ioanna Rannou; Pilios-Dimitris Stavrou; Panagiotis Ferentinos; Athanasios Douzenis; Nikolaos Smyrnis; Efthimia Gavriilidou; Rossetos Gournellis (Research in Psychotherapy)
Despite recent studies establishing self-compassion and secure attachment to be vital protective factors against suicidality, the role of attachment as a psychological mechanism that may mediate the relationship between self-compassion and suicidality has not been investigated to date. This study aims to address this gap by investigating whether attachment styles, specifically avoidant attachment, mediate the link between self-compassion and suicidality in patients with major depressive disorder (MDD). 273 adult patients with MDD completed the Suicidal Behaviors Questionnaire-Revised (SBQ-R), the Beck Depression Inventory (BDI-II), the Experiences in Close Relationships Scale (ECRS), and the Self-Compassion Scale (SCS) along with sociodemographic and clinical questions. Statistical analyses included correlation analysis and Mann- Whitney U tests to examine the relationships and possible differences between the non-suicidal group and the suicidal group of patients in terms of attachment style, self-compassion, and self-destructive behaviors. A mediation analysis to assess the role of attachment avoidance in the relationship between selfcompassion and suicidality was also conducted. Both attachment anxiety and avoidance were positively associated with suicidality and depression and negatively with self-compassion. The patients with increased suicidality differed significantly in the levels of depression, self-compassion, and attachment compared to those who were non-suicidal. The protective mechanism of self-compassion against suicidality was mediated by attachment avoidance. Research findings highlight the need for considering attachment-related issues to understand suicidality and tailor interventions in the field of suicide prevention and treatment while they gauge treatment priorities in working with depressed patients with suicidal thoughts and behaviors.